Formação continuada de professores: o olhar dos assistentes técnicos pedagógicos sobre os programas de formação continuada propostos pela Secretaria de Estado de Educação no período 2002/2006 - Brancaglion, Sonia Maria (2010)
With this work I tried to understand the point of view of the Technicians who worked on Pedagogical Training Program of the Ministry of Education, in the period 2002 to 2006, on this training program. Studying the point of view of these professionals on this program was a way to understand the place that I took while as a Teaching Assistant Technical Board of Education of the state system of education in São Paulo. For this study, I adopted a qualitative approach and as an instrument to collect data to document analysis, done through a literature review on the issue of training in recent decades. In this sense I sought support in Tardif (2002) Nóvoa (2002) Furlaneto (2003) Josso (2004) Schon (2004) among others. I also analyzed documents and legal texts that guided the organization and development of courses that made up the training program studied. Besides the document analysis resorted to reflection on my practice and experience of colleagues who, like me, also played this role in a Board of Education during the study period. The development of the work contributed to the debate about the place that I occupied as a Technical Assistant in the Educational Program of Continuing Education as well as other educators who were involved in this process saw their performance. Thus, I believe this work can constitute an important contribution to managers, teachers, researchers and people interested about teacher education generally and particularly in the state system of education, as it provides knowledge on these topics .